The Role Of I'rab In Eliminating Ambiguity Of Meaning In Arabic - Wati, Mahrida; Bahri, Samsul; An-Namir, Syihab (UIN ANTASARI, 2024)
Ambiguity (al-Ghumûdh) is the construction of words or sentences that have multiple meanings that sometimes cause confusion and misunderstanding in understanding and interpreting a sentence or idea. Ambiguity (al-Iltibâs) can occur at various linguistic levels or levels, namely: phonetic, lexical, and grammatical. The factors of ambiguity can be examined from the angle of lexicon, morphology, syntax, or structure. In Arabic, I'râb is one of the factors that cause ambiguity (al-Iltibâs) of meaning in the sentence (al-Jumlah). I'râb is one of the characteristics (al-Khashâ'ish) and uniqueness of the Arabic language which serves to eliminate ambiguity in the sentence (al-Jumlah). Keywords: Ambiguity, I'râb, Meaning